The Brand Strategies Of Airlines : A Study Of Malaysia Airlines - Kwong, Lawrence Ang Kian (2009)
This case study, which is the case analysis, situational analysis will be done on general external environment and the aviation industry in particular through techniques such as Porter Five Forces Analysis and Competitor Profile Matrix (CPM).